2017
DOI: 10.1016/j.actamat.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically-induced grain coarsening in gradient nano-grained copper

Abstract: Gradient nano-grained Cu subjected to tensile tests yields at a stress almost twice of that of the conventional coarse-grained Cu at or below the room temperature. Beyond the yield stress, a uniform plastic strain of larger than 30% can be achieved, accompanied by homogeneous grain coarsening in nano-grained surface layer.The observed grain coarsening may induce certaindegree of "strain softening". The measured grain coarsening rates strongly depend on temperature, stress and strain rate, suggesting that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 68 publications
0
39
1
Order By: Relevance
“…37) Similarly, a lower rate of mechanically induced grain growth was found for a reduction of testing temperatures, although the experiments were already performed at low homologous values. 74,79) For any prediction regarding the migration rate it is thus of interest to understand if a pure mechanically driven regime exists at all, or if thermal effects also need to be considered at comparably low testing temperatures, though their contribution may be limited.…”
Section: Effect Of Deformation Temperature On the Saturationmentioning
confidence: 99%
“…37) Similarly, a lower rate of mechanically induced grain growth was found for a reduction of testing temperatures, although the experiments were already performed at low homologous values. 74,79) For any prediction regarding the migration rate it is thus of interest to understand if a pure mechanically driven regime exists at all, or if thermal effects also need to be considered at comparably low testing temperatures, though their contribution may be limited.…”
Section: Effect Of Deformation Temperature On the Saturationmentioning
confidence: 99%
“…Comparisons of fatigue results among GNG Cu, annealed CG Cu and CG Cu demonstrate that tensioncompression asymmetry of GNG Cu is closely correlated with the microstructure of GNG layer. One prominent feature of GNG surface layer is characterized by highdensity dislocations and curved GBs, similar to those observed in nanostructured metals prepared by severe plastic deformation [4]. Previous studies have shown that tension-compression asymmetry with a mean stress amplitude of 25-44 MPa is still detected in UFG Cu fatigued in strain-controlled low-cycle regime (N f < 10 5 cycles) [20].…”
Section: Resultsmentioning
confidence: 53%
“…Gradient nanograined (GNG) metals, as a promising hierarchical structure with grain sizes spatially increasing from nanoscale in surface to coarse grain (CG) in core, have attracted considerable interests, due to their unusual combination of high strength and considerable ductility in tensile tests [1][2][3][4]. Their fatigue properties and behaviours under cyclic loading are also very essential, which determine their prospect of engineering application [5].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing rolling strain, an increase in the FWHM of the (111) diffraction peak is found in the majority of the deformed layers. Considering that stress-induced grain growth behavior is commonly observed in deformed nanostructured metals, even in the gradient microstructure [22,23], grain size should not increase FWHM values, and thus an increase in FWHM indicates dislocation accumulation in the deformed grains. It has also been observed that FWHM decreases in some deformed layers, especially in layers with small grain size.…”
Section: Resultsmentioning
confidence: 99%